Generation of Nkx2‐5/CreER transgenic mice for inducible Cre expression in developing hearts. Issue 8 (15th June 2017) - Ranjbarvaziri, Sara; Park, Shuin; Nguyen, Ngoc B.; Gilmore, William B.; Zhao, Peng; Ardehali, Reza
Summary: Nkx2‐5 is a homeobox‐containing transcriptional regulator that serves as one of the earliest markers of cardiac lineage commitment. To study the role of Nkx2‐5‐expressing progenitors at specific time points in cardiac development, we have generated a novel and inducible NKX2‐5 mouse line by knocking in a CreER cassette into the Nkx2‐5 genomic locus, while preserving the endogenous Nkx2‐5 gene to avoid haploinsufficiency. We evaluated the specificity and efficiency of CreER activity after 4‐OHT injection by crossing Nkx2‐5 CreER/+ mice with a Rosa26 tdT/+ reporter strain. Our immunohistochemistry results confirmed Cre‐induced tdTomato expression specifically in cells expressing Nkx2‐5. These cells were mainly cardiomyocytes and were observed in the embryonic heart as early as day 9.5. Additionally, quantitative polymerase chain reaction on postnatal hearts showed enriched expression of Nkx2‐5 in isolated tdTomato‐expressing cells. No tdTomato expression was observed in Nkx2‐5 CreER/+ ;Rosa26 tdT/+ mice in the absence of 4‐OHT, confirming the inducible nature of CreER activity. The Nkx2‐5/CreER mouse model described in this article will serve as an invaluable tool to trace myocardial lineage and to temporally induce genetic manipulation in a selective population of cardiac progenitors during embryonic development and in the adult heart.